공기순환방식과 찹쌀페이퍼를 이용한 김스낵의 영양성분과 품질 특성 - 유현희(Hyeon-Hee Yu); 이영민(Young-Min Lee); 김미나(Mina Kim); 김동혁(Donghyuk Kim); 이주영(Juyoung Lee); 이정희(Jounghee Lee) (동아시아식생활학회지, 2022)
The specific aim of this study was to make laver snacks(fried seaweed paper covered with glutinous rice) by using an air fryer and glutinous rice paper to maximize the taste and texture of the traditional laver snack while increasing production volume by shortening the drying time. We used glutinous rice paper to laver(seaweed) instead of glutinous rice paste. Additionally, we heated the dried laver(170℃, 5 minutes) in the air fryer instead of deep-frying(170℃, 5 seconds). The crude fat content was high in the deep-fried laver snack. However, the laver snack coated with glutinous rice paper instead of glutinous rice paste had reduced crude fat levels. Further, the laver snack coated with glutinous rice paste cooked in the air fryer had the lowest fat content. The contents of amino acids and minerals significantly increased in the laver snacks made using the air fryer by circulating hot air compared to the deep-fried version, but they significantly decreased when glutinous rice paste was replaced with glutinous rice paper. However, when the deep-frying process was replaced by the simultaneous use of glutinous rice paper and heating through circulation of hot air, we found that the nutrient contents of the laver snack was preserved to some extent but could not achieve the same level as that of the control. The results of the sensory evaluation of the laver snack coated with glutinous rice paste showed that the preference for color and flavor decreased when deep-frying was replaced with the heating through circulation of hot air method. The preference for texture decreased when glutinous rice paper was used instead of glutinous rice paste. However, with the simultaneous use of heating through circulation of hot air and glutinous rice paper, there were no differences observed compared to the original snack. In conclusion, the simultaneous use of heating through circulation of hot air and glutinous rice paper could improve the manufacturing process of the laver snack and its health functionality. KCI Citation Count: 0